2007
DOI: 10.7202/032738ar
|View full text |Cite
|
Sign up to set email alerts
|

Les terrasses de cryoplanation dans le nord du Yukon : distribution, genèse et âge

Abstract: Les terrasses de cryoplanation sont une forme fréquente et caractéristique dans le nord du Yukon. Plus de 1000 ont été identifiées dans les dolomies, les calcaires, les argilites et les quartzites de cette région. Situées sur des versants, elles dominent toujours des pediments. Elles ne sont jamais présentes sur des versants façonnés par l'érosion fluviale. Lagélifraction, lagélifluxion et le ruissellement aréolaire associés à l'existence de plaques de neige résiduelles paraissent être les processus les plus a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 8 publications
2
3
0
Order By: Relevance
“…Vague generalisations have resulted from relative-age dating based on morphostratigraphy, weathering-rind thickness, vegetation, or lichen cover (Péwé, 1970; Reger, 1975; Lauriol et al, 1997; Nelson, 1998). However, it has been concluded that they probably develop over very long periods of time, which supports similar ideas based on the observation that they are well developed in terrain that has never been glaciated or was not glaciated during the last glaciation (Reger and Péwé, 1976; Lauriol and Godbout, 1988; Nelson and Nyland, 2017). To the authors’ knowledge, the results of numerical-age dating techniques have been presented in two published papers only (Cremeens et al, 2005; Lauriol et al, 2006): the first applied 36 Cl cosmogenic-nuclide exposure-age dating to two possible cryoplanation summit flats; the second obtained nine 14 C dates from the regolith cover of the treads of undoubted cryoplanation terraces.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Vague generalisations have resulted from relative-age dating based on morphostratigraphy, weathering-rind thickness, vegetation, or lichen cover (Péwé, 1970; Reger, 1975; Lauriol et al, 1997; Nelson, 1998). However, it has been concluded that they probably develop over very long periods of time, which supports similar ideas based on the observation that they are well developed in terrain that has never been glaciated or was not glaciated during the last glaciation (Reger and Péwé, 1976; Lauriol and Godbout, 1988; Nelson and Nyland, 2017). To the authors’ knowledge, the results of numerical-age dating techniques have been presented in two published papers only (Cremeens et al, 2005; Lauriol et al, 2006): the first applied 36 Cl cosmogenic-nuclide exposure-age dating to two possible cryoplanation summit flats; the second obtained nine 14 C dates from the regolith cover of the treads of undoubted cryoplanation terraces.…”
Section: Discussionsupporting
confidence: 76%
“…However, although cryoplanation terraces have been widely recognised in regions with present or former nonglacial cold climates, such as Siberia (Boch and Krasnov, 1994; Demek, 1968; Czudek, 1995), Mongolia (Richter et al, 1963), Alaska (Reger and Péwé, 1976; Nelson, 1998; Nelson and Nyland, 2017), northern Canada (Lauriol and Godbout, 1988; Lauriol et al, 2006), Central Europe (Demek, 1969b; Traczyk and Migon, 2000; Křížek, 2007), Iceland (Schunke and Heckendorff, 1976; Schunke, 1977), the Andes (Grosso and Corte, 1991), Antarctica (Hall, 1997; Hall and André, 2010), and the British Isles (Te Punga, 1956; Waters, 1962), criteria for the recognition of active features are largely lacking. In the absence of dating evidence, moreover, most examples discussed in the literature are of unknown age, and many are regarded as relict.…”
Section: Introductionmentioning
confidence: 99%
“…These flat surfaces are developed in highly resistant argillites and chert of the Precambrian Neruokpuk Formation. Similar bedrock benches are described from elsewhere in Yukon (Hughes, 1990;Rampton, 1982;Lauriol and Godbout, 1988). Their problem of interpretation is compounded by the fact that quantitative field studies have yet to demonstrate the active formation of these terraces.…”
Section: Bevelled Summits and Erosional Benchessupporting
confidence: 52%
“…Similar bedrock benches are described from elsewhere in Yukon (Hughes, ; Rampton, ; Lauriol and Godbout, ). Their problem of interpretation is compounded by the fact that quantitative field studies have yet to demonstrate the active formation of these terraces.…”
Section: Discussionmentioning
confidence: 97%
“…CTs are prominent landforms throughout unglaciated portions of interior and western Alaska, 15,16 Yukon Territory, 17,18 and the Russian Far East, particularly Chukotka 19,20 . However, many unresolved questions about their genesis and developmental history remain 19,20 .…”
Section: Introductionmentioning
confidence: 99%